CGIAR GENDER Platform - Plan of Work and Budget 2021 - CGIAR GENDER Platform (CGIAR GENDER Impact Platform, 2021)
No major adjustments to the CGIAR GENDER Platform theory of change are anticipated in 2021. The Platform will continue to implement its vision of putting gender equality at the center of agricultural and food system transformation, through continued engagement with One CGIAR and with partners. The GENDER Platform will continue to work with all 14 CGIAR centers throughout 2021, moving into One CGIAR as it evolves.